(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Intracranial aneurysms (IAs) of the posterior circulation (PC) rupture more frequently and the morbidity and mortality rates are higher compared to anterior circulation. Morphological parameters such as dome neck width, size ratio (SR), believed to contribute significantly in determining the risk of rupture of intracranial aneurysms. Aims: To compare the morphometry of ruptured aneurysms between anterior and posterior circulation aneurysm in aneurysmal Subarachnoid haemorrhage (aSAH) patients. Methods: This analytical cross-sectional study was carried out in the department neurologyof National Institute of Neurosciences and Hospital, Dhaka. A total 110 patients of aneurysmal SAH confirmed by non-contrast CT scan of head having age more than 18 years, of both sexes and who gave consent were enrolled in this study. Morphologic parameter like neck width, maximum dome diameter (SR) and locations were recorded in the data collection sheet. Results: A total number of 110 patients were recruited after fulfilling inclusion and exclusion criteria. Of them two had normal findings in digital subtraction angiogram (DSA). Majority (31.5%) of the patients belonged to age group 50-59 years. Male and female ratio was 1:1.25. Regarding the morphology of aneurysm, 96 patients had aneurysm in anterior cerebral circulation and 12 patients had aneurysms in posterior cerebral circulation. Most of the aneurysms of anterior and posterior cerebral circulation were saccular in type. Fusiform aneurysms were found 3(3.1%) and 2(16.7%) in anterior and posterior cerebral circulation respectively with p value of 0.035. The mean neck width was 2.92±1.52 mm in anterior and 5.96±5.72 mm in posterior cerebral circulation(p<0.05). Conclusion: This study revealed neck width is found to be significant differentiating factor between intracerebral aneurysms of anterior and posterior cerebral circulation. Fusiform aneurysm is significantly higher in posterior circulation. There is no significant difference in clinical profile of patients of anterior and posterior circulation.